Red Betel Leaves Methanolic Extract (Piper crocatum Ruiz & Pav.) Increases Cytotoxic Effect of Doxorubicin on WiDr Colon Cancer Cells through Apoptosis Induction - Nindi Wulandari; Argandita Meiftasari; Hilyatul Fadliyah; Riris Istighfari Jenie (Indonesian Journal of Cancer Chemoprevention, 2018)
Doxorubicin is a chemotherapeutic agent that causes a lot of side effects in high doses. Thus, combination with a co-chemotherapeutic agent which can increase its toxicity on cancer cells, is needed to reduce its therapeutic dose. Red betel leaves (Piper crocatum Ruiz & Pav.) have been known to contain flavonoids and alkaloids that have anticancer activity. This study was conducted to determine the cytotoxic effect and apoptosis induction of red betel leaves methanolic extract (RBM), doxorubicin (dox) and the combination of them on WiDr cells as model of colon cancer. RBM was extracted by soxhlet method using methanol. Cytotoxicity assay was performed using MTT assay for both single and combination treatments for 24 hours to determine IC50 and CI as their parameters. Apoptosis induction was analyzed by double staining method using ethidium bromide-acridine orange staining. Treatment of RBM and dox on WiDr cells for 24 hours showed cytotoxic activity with IC50 100 μg/mL and 1.6 μM respectively. Combination of RBM and dox performed synergism effect with CI<0.9 (p<0.05). Combination of RBM (12.5 μg/mL) and dox (0.4 μM) increased the number of apoptosis cells compared to each single treatment. Based on this study, it can be concluded that red betel leaves methanolic extract is potential to be developed as a co-chemotherapeutic agent of doxorubicin on colon cancer but still need further study to disclose the underlying molecular mechanisms.Keywords :  Red betel leaves (Piper crocatum Ruiz & Pav.), doxorubicin, WiDr cells, co- chemotherapeutic agent